Enhancing Higher-Order Thinking Skills in Early Childhood Through APE Puzzle Hopscotch: A Quasi-Experimental Study - Wati Fajzrina, Lati Nurliana; Winarti; Fatimah; Andriani, Diana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study examines the influence of APE puzzle hopscotch on higher-order thinking skills (HOTS) in children aged 4-6 years at PAUD IT ADAR Kalasan DIY. Employing a quasi-experimental design, the research included an experimental group receiving the APE puzzle hopscotch intervention and a control group without any intervention. Over four months, pretest and posttest assessments were conducted to evaluate HOTS in both groups. The research instruments measured indicators across analysis (C4), evaluation (C5), and creation (C6). Results revealed significant enhancements in the experimental group’s HOTS, with N-Gain scores showing moderate effectiveness. Statistical tests confirmed the intervention's impact, demonstrating significant differences in post-test scores between the experimental and control groups (p < 0.05). The findings suggest that APE puzzle hopscotch effectively stimulates cognitive development in early childhood. Despite limitations such as a small sample size and short study duration, the study underscores the potential of interactive educational tools in enhancing critical thinking and problem-solving skills. Implications for educational practice include the integration of engaging tools into curricula to foster HOTS. Future research should address the current study's limitations, validate the findings across different settings, and explore the effects on other developmental areas. Additionally, longitudinal studies could provide deeper insights into the long-term benefits of such educational tools. This research contributes to the ongoing discourse on the importance of innovative teaching strategies in early childhood education, emphasizing the role of interactive play in cognitive growth.